FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU PENDIDIKAN JASMANI DI SEKOLAH DASAR - J. S. Husdarta, - (2006)
Background of this study is related to low performance of elementary school physical education teachers. Teachers' performance is influenced by such factors as supervision service, principals' leadership, and sufficient instructional facilities. With the support of these factors, the performance of elementary school physical education teachers can be improved. Related to these central issues, the study has identifies specific factors which might influence teachers' performance. According to theories, the improvement of teachers' performance must be done by considering internal and external factors of the teachers. There were five variables that could have effects on teachers' performance: (I) supervision service, (2) principals' leadership, (3) sufficient representative instructional facilities, (4) competences, and (5) achievement motivation.Method used in this study was a descriptive method accompanied with a questionnaire. Sample of the study was 150 physical education teachers using a random sampling technique.The result of this study showed that the following factors have influenced the performance of physical education teachers: (1) 5,70% of supervision service, (2) 17,10% of principals' leadership, (3) 6,10% of sufficient instructional facilities, (4) 13,90% of competences, and (5) 12,60% of achievement motivation. The influence of those factors was 55,40% in total, and the remaining 44,60% was caused by other variables.The conclusion is that factors which have influence the performance of physical education teachers have not worked optimally. Hence, principals and physical education teachers have to work together in a synergic way to attain the institutional goals.